Analysis of the state of surface water of Poltava region in control sites - Степова, О. В.; Булавенко, Р. В.; Рома, В. В. (Scientific Progress & Innovations, 2012)
The ecological estimation of a condition of river waters of Poltava region in areas of placing of treatment facilities which has allowed to estimate a situation developed in investigated water objects is spent and to classify them on degree of suitability for water use principal views. The estimation of quality of surface water was carried out on the basis of the analysis of the information of sizes of hydrochemical indicators in comparison with their corresponding values of maximum permissible concentration.